Processing in a nutshell - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Decortication of tropical oilseeds and edible nuts by G S Pinson D J Melville and D R S Cox 1991 38pp UKL33.00 ISBN 0 85954 290 4 pbk NRI Publications Central Avenue, Chatham Maritime Kent ME4 4TB, UK